Control Transfers, Privatization, and Corporate Performance: Efficiency Gains in China's Listed Companies - Chen, Gongmeng; Firth, Michael; Xin, Yu; Xu, Liping (Journal of Financial and Quantitative Analysis, 2008)
Abstract We investigate performance effects for China's listed firms when there is a change in the controlling shareholder. These changes include ownership transfers from one state entity to another state entity and from a state entity to a private entity. We find positive performance effects when control is passed to a private entity. In contrast, when the transfer is made to another branch of the state, there is little change in performance. The stock market responds positively to a change in control, with the largest effect observed for private transfers. Our results suggest the Chinese government should continue to sell down its share ownership in listed firms as the transfer of control to private owners enhances corporate profitability and efficiency. Moreover, to help ownership reform, China should encourage an active market for corporate control.